The effect of endodontic filling agents on the activity of the regeneration processes of bone tissue in the experiment - Han, Iryna; Musij-Sementsiv, Khristina; Zubachyk, Volodymyr (Journal of Medical Science, 2018)
Introduction. Highly important is to regenerate the inflammatory destructive processes of bone tissue outside the apical area of the tooth that would optimize reparative bone formation, mineralization of tooth tissues, restoration of periodontal function and stability of tooth to occlusive loads, especially with acquired extensive root apex. Low efficiency of endodontic treatment led to the searching of the new osteotropic drugs of osteoconductive action and biorevitalization to stimulate the repairing and regeneration of tissues outside the apical area and dense obturation of the apex of the tooth root.Aim. of our research was to determine the dynamics of reparative processes in the bone tissue under the influence of drugs and compositions for endodontic treatment based on an analysis of indicators of a mineral metabolism, marker enzymes and an activity of antioxidant system and lipid peroxidation.Material and Methods. An experiment was conducted on 120 white rats. It was created a bone defect, which was filled with studied biomaterials or left with a blood clot. From the experiment the rats were taken out on 14 and 90 day. In homogenates of bone tissue it was examined the activity of lysosomal enzymes — alkaline (ALP) and acid (AP) phosphatases and the content of microelements — calcium and phosphorus. In the blood of rats it was studied the concentration of general protein, lipid peroxidation products — malonic dialdehyde (MDA) and the enzyme activity of antioxidant system — catalase (CAT) and superoxide dismutase (SOD).Results and conclusions. Results of conducted experimental research of the effect of endodontic filling materials on the activity of the regeneration processes of bone tissue show that proposed compositions based on hydroxyapatite and beta-tricalcium phosphate, due to their osteoconductive and biorevitalization qualities, promote more active stimulation of bone tissue regeneration processes compared to generally accepted drugs.
Keywords: experiment; biomaterials; regeneration; alkaline phosphatase; acid phosphatase; calcium; phosphorus; malonic dialdehyde; catalase; superoxide dismutase; general protein